Obstructive Nephropathy from Misplaced Suprapubic Catheter with Antegrade Migration into the Urethra - Alexander W. Lipinski; Jordan R. Pollock; Nelly Tan; Douglas Rappaport (Clinical Practice and Cases in Emergency Medicine)
Case Presentation: An 83-year-old male with a history of prostate cancer and prior prostatectomy presented with lower abdominal pain, urethral leakage, and hematuria after a routine suprapubic catheter exchange, which was found to be incorrectly positioned in the bulbar urethra, leading to obstructive nephropathy with mild hydronephrosis. Discussion: This case highlights the increased risk of suprapubic catheter misplacement and complications in elderly patients with neurogenic bladder and altered urinary anatomy, particularly after prostatectomy and artificial urethral sphincter placement. It emphasizes the importance of careful management during catheter exchanges in such patients to prevent complications of misplacement.